Modeling Complementarity in Monopolistic Competition - Kiminori Matsuyama (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
In recent years, monopolistic competition models have frequently been applied in macroeconomics, international and interregional economics, and economic growth and development. In this paper, I presenta highly selective review in this area, with special emphasis on the complementarity and its role of generating multiplier processes, agglomeration, underdevelopment traps, regional disparities, and sustainable growth, or more generally, what Myrdal (1957) called the "principle of circular and cumulative causation."
Keywords: 330